Brand Community dalam Meningkatkan Loyalitas Merek pada Sepeda Motor Yamaha Vixion Wilayah Jawa Tengah dan Daerah Istimewa Yogyakarta - Yuyun Wahyuni; Kunto Wibisono; Suliantoro Suliantoro; Indra Ade Aprilia (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2023)
Competition between companies is very tight. Companies are required to work hard to retain their customers. The purpose of this study was to determine the significance of the influence of brand community: legitimacy (X1), opposition brand loyalty (X2), celebrating brand history (X3), sharing brand stories (X4), integrating and retaining members (X5), and assisting in brand use. (X6) on brand loyalty (Y) on Yamaha Vixion motorbikes in the Central Java and Yogyakarta Special Region regions. The object of this research is the Yamaha Vixion community in Central Java and the Special Region of Yogyakarta. The data used is primary data with a questionnaire sampling technique. The population is 228 people with a sample size obtained using the Slovin formula of 150 respondents. The instrument test tool uses validity and reliability tests. The analysis tool uses multiple linear regression. Test the hypothesis using the t test and F test. The results of the study show that the brand community consists of: legitimacy (X1), opposition brand loyalty (X2), celebrating brand history (X3), sharing brand stories (X4), integrating and retaining members (X5), and assisting in brand use ( X6) has a significant effect on brand loyalty (Y) on Yamaha Vixion motorbikes in the Central Java and Yogyakarta Special Region regions. The coefficient of determination obtained from the adjusted R square value of 60.3% indicates that the research contributes 60.3%, while the remaining 39.7% is influenced by other variables not included in this research model.